EFFECTIVE PROSPECTS FOR IMPLEMENTING DIGITAL GOVERNANCE IN THE ENTERPRISES (American Journal of Business Management, Economics and Banking, 2024)
This article deals with the importance, stages and benefits of implementing digital governance in enterprises. Digital management includes modern management systems that serve to optimize business processes, accelerate decision-making and increase efficiency. The article describes the main stages of the digital transformation process - analysis of technological opportunities, data digitalization, implementation of automation systems, personnel training and constant monitoring. It also analyzes the role of digital governance in increasing efficiency, reducing costs, and ensuring competitiveness for businesses. The article serves as a useful guide for entrepreneurs and managers interested in implementing digital technologies.